CFD modelling of a small–scale fixed multi–chamber OWC device. (July 2019) - Shalby, Mohammad; Elhanafi, Ahmed; Walker, Paul; Dorrell, David G.
Abstract: Wave Energy Converters (WECs) have excellent potential as a source of renewable energy that is yet to be commercially realised. Recent attention has focused on the installation of Oscillating Water Column (OWC) devices as a part of harbor walls to provide advantages of cost–sharing structures and proximity of power generation facilities to existing infrastructure. In this paper, an incompressible three–dimensional CFD model is constructed to simulate a fixed Multi–Chamber OWC (MC–OWC) device. The CFD model is validated; the simulation results are found to be in good agreement with experimental results obtained from a scale physical model tested in a wave tank. The validated CFD model is then used for a benchmark study of 96 numerical tests. These investigate the effects of the PTO damping caused by the power take–off (PTO) system on device performance. The performance is assessed for a range of regular wave heights and periods. The results demonstrate that a PTO system with an intermediate damping can be used for all chambers in the MC–OWC device for most wave period ranges, except for the long wave periods. These require a higher PTO damping. An increased incident wave height reduces the device capture width ratio, but there is a noticeable improvement for long wave periods.